Pengaruh Kinerja Lingkungan Dan Biaya Lingkungan Terhadap Kinerja Keuangan Dengan Leverage Sebagai Variabel Intervening - Ade Mahendra Tarigan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to demonstrate the impact of Environmental Performance and Environmental Costs on Financial Performance and Leverage as Intervening variables in manufacturing companies listed on the Indonesian Stock Exchange throughout the period of 2019-2021.This research falls under the category of quantitative research, utilizing secondary data sourced from financial reports or annual reports released by companies listed on the Indonesian Stock Exchange. The data gathering method employed is the purposive sampling technique, with a selection criterion of 50 companies. This results in a total of 150 data points available for analysis. This study employs descriptive analysis techniques and utilizes the SPSS v26 software for data analysis. Based on the findings of this study, only three hypotheses were confirmed, while the remaining four were disproven. There is no correlation between Environmental Performance and Leverage, but Environmental Costs do have an impact on Leverage. On the other hand, Environmental Performance does influence Financial Performance, while Environmental Costs do not. Financial performance is not influenced by leverage. The relationship between Environmental Performance and Financial Performance is not influenced by Leverage, and Leverage is not considered an Intervening variable. However, there is a significant influence of Environmental Costs on Financial Performance.